Determination of Element Contents and Health Risk Assessment of Some Commercial Coffees in Türkiye - Demir, Funda; Uygunoz, Deniz; Kipcak, Azmi Seyhun; Derun, Emek (UNIV NAMIK KEMAL, 2025)
Coffee is one of the most consumed beverages worldwide, which has become an integral part of people's daily lives. The increasing demand for coffee consumption has led to the creation of many coffee brands producing various types of coffee around the world. One of the reasons for the widespread consumption of coffee is that it contains elements necessary for human health. Supplementation of food intake with essential minerals, which are present in large quantities in the body, and trace minerals, which are present in smaller quantities, is an important parameter in nutrition. Determining the total concentrations of the elements in coffee allows the assessment of its nutritive quality and at the same time, its adverse effects on human health can be decided. In the present study, essential-zinc (Zn), selenium (Se), phosphorus (P), sodium (Na), manganese (Mn), magnesium (Mg), potassium (K), iron (Fe), copper (Cu), chromium (Cr), cobalt (Co), calcium (Ca) and boron (B)-and non-essential-titanium (Ti), antimony (Sb), lead (Pb), nickel (Ni), molybdenum (Mo), cadmium (Cd), barium (Ba), arsenic (As) and aluminium (Al)-element content in some coffee types from different brands was analyzed by inductively coupled plasma-optical emission spectroscopy (ICP-OES) and the results were interpreted in terms of human health. Percentages of elements ingested with daily consumption of 300 mL of selected coffee types were also calculated on a person-by-person basis according to gender. Health risk assessment was performed involving carcinogenic risk and non-carcinogenic risk evaluation. In all coffee types, K element concentration has been reported as the highest element. As, Cd, Mo, Sb, and Ti elements were not detected in all types of coffees. A female's highest daily element intake percentage is Mg for all types of coffee with the highest concentration of 15.561% (decaffeinated coffee, P1). For a male, the Mg element daily intake percentage is also the highest except Milicano and filter coffee of P2 and Turkish coffee of P4. The hazard index (HI) of all samples was less than 1, thus, daily consumption of 300 mL of these coffees is defined in a low-risk group. The target carcinogenic risk (TCR) value was calculated below 1x10-4 for all coffee types except Classic (Product 1). Classic coffee of Product 1 should be consumed less than 300 mL/day since its TCR value is higher than 1x10-4.
Keywords: Coffee; Essential and non-essential elements; ICP-OES; Risk assessment; WATER; Agriculture